2011
DOI: 10.1002/jcb.23243
|View full text |Cite
|
Sign up to set email alerts
|

PI3K/Akt responses to oxytocin stimulation in Caco2BB gut cells

Abstract: Recently, we discovered oxytocin receptor (OTR) expression in the developing gut villus epithelium that emerges in villus-crypt junctions after weaning. Oxytocin (OT) and OTR regulate many physiological functions in various tissues; however, their function in gut epithelium is unknown. We explored responses of PI3K and Akt phosphoisoforms to OT stimuli in the Caco2BB human gut cell line. In Caco2BB cells, PI3K and pAkt levels peaked at 62.5  nM OT. At higher concentrations, PI3K decreased more gradually than p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 39 publications
3
21
0
Order By: Relevance
“…At the cellular level, in vitro experiments using a gut cell line have demonstrated that OT modulates important molecules in the stress signalling pathway (Klein, Tamir, Hirschberg, Glickstein, & Welch, 2013;Klein, Tamir, & Welch, 2011) and plays a regulatory role in translation of proteins (Klein et al, 2014). These studies suggest that biochemical factors in milk, including exogenous OT from the mother, play an important role in the unfolded protein response to reduce cellular stress.…”
Section: Visceral Oxytocin and Emotional Behaviormentioning
confidence: 99%
“…At the cellular level, in vitro experiments using a gut cell line have demonstrated that OT modulates important molecules in the stress signalling pathway (Klein, Tamir, Hirschberg, Glickstein, & Welch, 2013;Klein, Tamir, & Welch, 2011) and plays a regulatory role in translation of proteins (Klein et al, 2014). These studies suggest that biochemical factors in milk, including exogenous OT from the mother, play an important role in the unfolded protein response to reduce cellular stress.…”
Section: Visceral Oxytocin and Emotional Behaviormentioning
confidence: 99%
“…Subsequently, we found that OT attenuated the stimulation of the PI3K/Akt pathway induced by fresh growth medium (FGM) (Klein et al 2013). OT also modulated the phosphatase and tensin homolog (PTEN) (Klein et al 2011) and the mammalian target of rapamycin (mTOR) pathway (Klein et al 2013). Several of these OTR signal transducers are associated with both ASD and protein translation; mutations in PI3K, PTEN, and tuberosclerosis protein (TSC2), members of the Akt/mammalian target of rapamycin complex 1 (mTORC1) pathway that control ribosomal protein and translation factor activity have been linked with ASD (Kelleher and Bear 2008).…”
Section: Introductionmentioning
confidence: 94%
“…We analyzed the response of the mTORC1 substrate 4E-BP1, a negative regulator of eIF4E, to test whether OT influences translation factors downstream of mTORC1. For all experiments, we have defined high (62.5 nM) and low (7.8 nM) concentrations of OT based upon convention from our prior work (Klein et al 2011) where high 62.5 nM OT maximally stimulated the Akt/PI3K pathways. Protein extracts from Caco2BB cells treated with high or low concentrations of OT for 30 min were fractionated by capillary electrophoresis and analyzed for phosphorylation.…”
Section: Ot Modulates Phosphorylation Of 4e-bp1mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies suggest that, in addition to its role in the brain, OXT may also have an important neuromodulatory role in the gut by activating the PI3K/Akt pathway in a dose-and time-dependent manner [164]. Our lab has found decreased plasma oxytocin in individuals with autism, and these oxytocin levels correlated with high mTOR, suggesting a possible relationship between oxytocin and aberrant Akt pathway signaling [128].…”
Section: Oxytocinmentioning
confidence: 96%